THE SPREAD OF CHINA’S CULTURAL SOFT POWER THROUGH THE CHINESE NEW YEAR FESTIVAL IN PONTIANAK - Thedeus, Kevin; Nuraeni, Nuraeni (UI Scholars Hub, 2025)
Chinese New Year (CNY) celebration is one of the biggest celebrations for the Chinese Indonesians in Pontianak. This celebration allows the Chinese ethnic groups to remember and maintain their traditional roots while living in the host country. However, the high interest from non-Chinese Indonesians in visiting and participating in the CNY celebration raises questions about whether this diasporic activity unintentionally strengthens the favourability of the Indonesian people towards China and is used as a means of China's soft power. This study will discuss the spread of culture from the CNY Festival in Pontianak, which can serve as an instrument of China's soft power. This study uses a quantitative method through a survey of 384 samples and simple linear regression analysis. The variables used in this study are the Love of Listening to Music (Y1) and the Desire to Learn Mandarin (Y2), with the X variable being the CNY Festival. The research shows that the CNY Festival that is hosted by the Chinese community actually attracts and gives a positive impression of Chinese music and Mandarin language to native Indonesians, hence creating interest in Chinese music and the will to learn Mandarin. If utilised well, the diaspora can become a new soft power instrument for China.